Media strategies of professional football clubs - Bekurov, R. V.; Lingzhi, L.; Maryna, L. P. (Theory and Practice of Physical Culture, 2022)
Article attempts to analyze the functionality of club media of leading Russian and European football clubs. In particular, the material includes a reasoned, case-based assumption about the need for a media component in the structures of such organizations, regardless of their status.